Principles of interpretation, to be applied to the common VAT system: The ambivalence between the teleological element, in what concerns the principle of tax avoidance and the interpretation of rules prescribing exemptions and lower rates (De Legibus - Law Journal, 2024)
This work aims to describe the main methods of interpreting the rules that apply VAT exemptions and reduced rates and to outline the difference in treatment of the teleological element, provided by the European Court of Justice, when applying such interpretations standards and when employing the principle of tax avoidance.
Keywords: Value Added Tax. Interpretation of the law. Provisions concerning exemptions. Provisions concerning lower tax rates. Abuse of law.